Three decades of soil microbial biomass studies in Brazilian ecosystems: Lessons learned about soil quality and indications for improving sustainability - Kaschuk, Glaciela; Alberton, Odair; Hungria, Mariangela (Soil biology & biochemistry, 2010)
Soil microbial biomass plays important roles in nutrient cycling, plant–pathogen suppression, decomposition of residues and degradation of pollutants; therefore, it is often regarded as a good indicator of soil quality. We reviewed more than a hundred studies in which microbial biomass-C (MB-C), microbial quotient (MB-C/TSOC, total soil organic carbon) and metabolic quotient ( qCO 2) were evaluated with the objective of understanding MB-C responses to various soil-management practices in Brazilian ecosystems. These practices included tillage systems, crop rotations, pastures, organic farming, inputs of industrial residues and urban sewage sludge, applications of agrochemicals and burning. With a meta-analysis of 233 data points, we confirmed the benefits of no-tillage in preserving MB-C and reducing qCO 2 in comparison to conventional tillage. A large number of studies described increases in MB-C and MB-C/TSOC due to permanent organic farming, also benefits from crop rotations particularly with several species involved, whereas application of agrochemicals and burning severely disturbed soil microbial communities. The MB-C decreased in overgrazed pastures, but increased in pastures rotated with well-managed crops. Responses of MB-C, MB-C/TSOC and qCO 2 to amendment with organic industrial residues varied with residue type, dose applied and soil texture. In conclusion, MB-C and related parameters were, indeed, useful indicators of soil quality in various Brazilian ecosystems. However, direct relationships between MB-C and nutrient-cycling dynamics, microbial diversity and functionality are still unclear. Further studies are needed to develop strategies to maximize beneficial effects of microbial communities on soil fertility and crop productivity.